Sociological monitoring of customer satisfaction with the quality of the educational services - G. . Gaidukova (Высшее образование в России)
The article focuses on the properties and characteristics of the educational process, which determine its ability to respond to the educational needs of specific customers. Satisfaction with the quality of educational services of the main consumers (applicants, students andemployers) is characterized. The key problems, decreasing customer satisfaction: omissionsin the career-guidance work; lack of opportunities in the choice of specialization and optional disciplines; weak provision with educational-methodical literature; poor quality of supply; lack of practical training have been identified.